ChemInform Abstract: Methodology to Access Tetrahydrodipyridoimidazole Derivatives. Issue 2 (9th January 2013) - El Bousmaqui, Mohamed; Donnier‐Marechal, Marion; Larchanche, Paul‐Emmanuel; Melnyk, Patricia; Carato, Pascal
Abstract Title compounds (VI) are synthesized starting from amine (I) and aldehyde (II) using Bischler—Napieralski or Pictet—Spengler reactions as key reactions.